(untitled) (Research, Society and Development, 2021)
Introduction: Alopecia is the temporary or congenital absence of hair or hair and can be classified as scarred and non-scarred. This study focused on the comparative analysis of the treatments of androgenetic alopecia areata, which are non-scarring alopecia. Androgenetic alopecia is the most common form of hair loss in humans and alopecia areata has around 2% worldwide. Objective: The study aimed to know, correlate and compare the different forms of treatment for andeatetic alopecia areata in the most recent studies. Method: This is a systematic review of scientific articles published in the PUBMED database between 01/01/2018 and 12/31/2018. The keywords "alopecia areata and treatment" and "alopecia androgenetic and treatment" were used. First, the articles were analyzed by title and abstract by two reviewers (BMSS and TJ), and in case of disagreement, a third reviewer was consulted (RAN). Afterwards, there was a complete reading of the texts, and in case of disagreement, a last reviewer was consulted (RAN). Results: The search for "alopecia areata and treatment" resulted in 26 records, of which 14 were excluded. After reading the full articles, of the 12 articles, only seven were used. The search for "alopecia androgenetic and treatment" resulted in out of 84 records, of which 61 articles did not meet the inclusion criteria.After reading the 24 articles, only nine were selected.After the selection phase, 16 articles remained eligible. Conclusion: There is a wide range of treatments for alopecia, showing that the treatment should be individualized for each patient.Always remember to associate pharmacological therapy with psychological follow-up, since hair is also a communication tool.